PKM TEKNIK PENGENDALIAN ORGANISME PENGGANGGU TUMBUHAN (OPT) SEREALIA DI DESA SENANING KECAMATAN PEMAYUNG - Laksono, Bangun Joko; Enita, Enita; Uliya, Uliya; Purnomo, Dian; Roosseno, Roosseno (Nindikayla Institute, 2023)
Various factors, including site-specific, determine the key to the success of pest control, carried out in a vast expanse, simultaneously and with good coordination between relevant agencies/officials, and the active role of farmers. Therefore, it is necessary to compile field references. The Directorate of Food Crop Protection, as the institution responsible for pest control, issued the OPT Control Technical Guidelines. This technical guide is expected to be used as a guide by stakeholders in terms of controlling OPT. Plant-disturbing organisms are found in many cereal plants. Cereals are grass-type plants producing starchy seeds that are usually processed into food. Cereals or cereals are plant species of rice-grain and grass-grass-grass-cultivated to produce grains. The objectives of implementing Community Service are (1). To find out the organisms that interfere with cereals, (2). To perfect and prevent the attack of organisms on cereals, (3). To carry out treatment of cereals that disturbing organisms have attacked. The principle of controlling plant pests developed today is to reduce the number of pest populations that attack plants to a population level that is not harmful. The components of OPT control that can be applied to achieve these objectives include (1). Physical control of OPT, (2). Mechanical Control of OPT.